Budaya Literasi Siswa dalam Program Membaca Mingguan di MTs NU 01 Batang - Tantri Cantrika Dewi; Elsya Lailatul Farikhah; Gladis Florensia Ananda Fauzi; Safita Revi Mariska; Rissa Shofiani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Literacy culture plays an important role in improving students’ reading skills and comprehension abilities. This study aims to describe students’ literacy culture through the weekly reading program at MTs NU 01 Batang. The study employed a qualitative approach using a descriptive method. Data were collected through observations, interviews, and documentation involving teachers, students, and library staff. The findings revealed that the weekly reading program is conducted regularly every Friday with teacher supervision and support from school library facilities. Literacy activities include reading books, writing summaries, and retelling the content of the reading materials. The program has a positive impact on increasing students’ reading interest, knowledge, information comprehension, and learning focus. Supporting factors include teachers’ active involvement, the availability of literacy facilities, and appreciation given to students. However, several challenges remain, such as the low reading interest of some students and limited collections of certain books. The weekly reading program has contributed significantly to fostering a literacy culture among students at school.